Pengaruh Penerapan Total Quality Management (TQM) dan Komitmen Organisasi terhadap Kinerja Perusahaan dengan Budaya Organisasi Sebagai Variabel Moderasi (Survei padaPerusahaan Manufaktur di Jawa Barat yang Listing di BEI) - Yenni Carolina (Universitas Kristen Maranatha, 2012)
This research aims to analyze the effect of TQM implementation and commitment organization toward company performance and the effect of organization culture as moderating variable toward the relationship among TQM implementation, commitment organization and company performance. This research is conducted by explanatory survey to all 32 manufacture companies in West Java which have listed at Indonesia Stock Exchange and have positive value of Return on Assets. The data collection used the questioner as a research instrument and supported by the interview and documentation. The Rank Spearman and Split Half Spearman – Brown were used to test the validity and reliability of the data. The data analysis of hypothesis testing is used the Simple Regression Analysis and Moderated Regression Analysis (MRA). The result indicates that TQM implementation and commitment organization have influenced the company performance. Organization culture which is moderating variable has influenced toward the relationship among TQM implementation, commitment organization and company performance.